Kesejahteraan Mental Karyawan dalam Era Digital: Dampak Teknologi pada Kesejahteraan Mental Karyawan dan Upaya untuk Mengatasi Stres Digital - Annisa Maharani; Ahmad Zeifuddin; Dyah Ayu Safitri; Hilya Sania Rosada; M Isa Anshori (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
Purpose – Using a Literature Review, the purpose of this research is to see and discuss the negative impact of emerging digital technology on the mental well-being of employees. Next, this article explores various efforts that can be made to overcome digital stress, both efforts that can be made by companies, leaders and managers, as well as employees themselves. Design/methodology/approach – Directed literature review is carried out to search for relevant sources on Google Scholar to form the basis of research. Findings – Based on these findings, technological advances in the world of work have been proven to be able to increase productivity and provide access to the desired information. However, excessive use of technology can actually have a negative impact on employees' mental health due to digital stress. Therefore, it is necessary to implement measures that can be taken to help overcome this. Originality/value – Apart from conducting a LR analysis of the problems to be discussed, which are limited in the field, this paper also underlines the need for ongoing discussions apart from previous discussions to increase our understanding of the impact of digital stress.